2010
DOI: 10.1177/0095798409359774
|View full text |Cite
|
Sign up to set email alerts
|

Proactively Addressing the Shortage of Blacks in Psychology: Highlighting the School Psychology Subfield

Abstract: To circumvent the disproportionately low number of persons of African descent in psychology, this study offers strategies for recruiting and retaining Black students and professionals. Data for this study were collected from 44 Black students and 3 Black faculty. Participants responded to questions that inquired about their perspectives regarding (a) effective recruitment and retention strategies, (b) being the vast minority in school/work settings, and (c) counselor race-ethnicity. Data were analyzed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 28 publications
3
86
0
Order By: Relevance
“…Chandler, 2011). These strategies may include offering undergraduate courses in school psychology, providing opportunities for students to work with school-based practitioners prior to graduate school, reaching out to high school students through career fairs and mentoring activities, and visiting undergraduate classrooms (Proctor et al, 2014).…”
Section: Tier 1 Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chandler, 2011). These strategies may include offering undergraduate courses in school psychology, providing opportunities for students to work with school-based practitioners prior to graduate school, reaching out to high school students through career fairs and mentoring activities, and visiting undergraduate classrooms (Proctor et al, 2014).…”
Section: Tier 1 Supportsmentioning
confidence: 99%
“…Ultimately, students from minority backgrounds may express interest in resources and supports to assist them in developing coping strategies (e.g. Chandler, 2011).…”
Section: Tiers 2 Supportsmentioning
confidence: 99%
“…For instance, Chandler (2011) investigated 44 Black students' and three Black faculty members' at three HBCUs beliefs about effective minority student recruitment and retention strategies in school psychology programs, as well as their awareness of school psychology. Major theme findings suggested that school psychology programs should offer financial support; connect to the Black community using minority focused research, Black-specific recruitment strategies, and intraracial mentorship; and increase awareness since most participants were not familiar with the profession.…”
Section: Recruitment Of Diverse Psychology Graduate Studentsmentioning
confidence: 99%
“…When selecting programs, AASPs sampled chose programs close to their established residences, primarily to maintain sources of familial and community support. Like participants in Chandler (2011), AASPs sampled believed those within school psychology must strategically recruit graduate students of color, particularly by raising awareness with children of color as early as elementary school and creating connections with HBCUs. Additionally, AASPs sampled felt that potential graduate students of color must perceive that support will be available for them within programs.…”
Section: Recruitment Of Diverse Psychology Graduate Studentsmentioning
confidence: 99%
See 1 more Smart Citation